2000
DOI: 10.1023/a:1008955722425
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: These findings suggest that one or more exposures or characteristics that differ between Japanese migrants and their descendants affect the development of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(25 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Our findings confirm past observations of substantially higher rates in foreign-born Japanese than Non-Hispanic Whites (74.6 vs. 52.8 per 100,000, respectively, in our study). Our results are in line with those of some (16) but not all (34) previous studies. In the latter study, unknown birthplace was imputed assuming the distribution for cases with known birthplace, which may bias the estimates.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings confirm past observations of substantially higher rates in foreign-born Japanese than Non-Hispanic Whites (74.6 vs. 52.8 per 100,000, respectively, in our study). Our results are in line with those of some (16) but not all (34) previous studies. In the latter study, unknown birthplace was imputed assuming the distribution for cases with known birthplace, which may bias the estimates.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have shown that invasive CRC incidence rates are usually but not always higher among Asian-Americans than in Asia (34,35). This general pattern is consistent with our observation of significantly higher CRC rates among US-born Filipinos and US-born Chinese men relative to their foreign-born counterparts, but is not consistent with our observations of similar rates between US-born and foreign-born Chinese women, and higher rates among foreign-born than US-born Japanese women and men.…”
Section: Discussionmentioning
confidence: 97%
“…This may be due in part to the greater availability of CRC screening in the United States compared with in some Asian countries that cannot afford to screen all those at risk [17]. Higher exposure to high-fat diets in Asian Americans may also contribute to higher prevalence of adenoma along with the risk of CRC [9,11,18].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, Asian countries have reported lower incidence of CRC compared with their Western counterparts, but the incidence of CRC has been rapidly increasing in many Asian countries [2][3][4]. Asian ethnic populations in the United States also appear to have higher incidence of CRC compared with Asian populations in Asian countries [5][6][7][8] and descendants of migrants who move from low-to high-risk regions appear to acquire higher rates of CRC [9]. Dietary and behavioral risk factors may be responsible for some of these differences [4,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been observed that migrants to developed countries tend to acquire the higher risk of cancer of their host country [3]. Further, the rates for second-generation migrants can be double that of the first [6]. It may be reasonable, therefore, to describe these diseases, including colorectal cancer, as diseases of civilization in which a number of acquired risk factors associated with civilization are implicated.…”
Section: Epidemiology: Civilization and Colorectal Cancer Incidencementioning
confidence: 99%